Promoted Disappearance of CO2 Hydrate Self-Preservation Effect by Surfactant SDS - Xueping Chen; Shuaijun Li; Peng Zhang; Wenting Chen; Qingbai Wu; Jing Zhan; Yingmei Wang (Energies, 2021)
The capture, storage and utilization of CO2 through hydrate-related technology is a promising approach to addressing the global warming issue. Dissociation is required after the transportation of CO2 gas in the form of a self-preserving hydrate. In order to investigate the dissociation behaviors as the self-preservation effect is removed, CO2 hydrates were frozen, and then the self-preservation effect was removed through uniform heating. An evident dependence of hydrate dissociation duration on the initial dissociation rates after losing the preservation effect was observed. The results in the silica gel powder and sodium dodecyl sulphate solution showed significant reductions in the initial dissociation temperatures and a slight decrease in the initial dissociation rates when compared with those of pure water. The reductions in the former were 2.88, 2.89, and 5.73 °C in silica gel, sodium dodecyl sulphate, and a combination of the two, respectively, while the reductions in the latter were 0.12, 0.12, and 0.16 mmol/min, respectively. As the results are inconsistent with the conventional mechanism elucidating a self-preservation effect, the ice shell theory was hence further supplemented by introducing innovative contribution factors—nonenclathrated liquid water and gas molecules dissolved inside. These findings are expected to provide references for CO2 gas transportation and usage of the self-preservation effect.